REPLACING THE JUDICIAL CONTROL WITH THE PREVENTIVE ARREST - George Octavian NICOLAE (Challenges of the Knowledge Society)
In the practive of the courts, there are situations where, due to a violation of the obligations imposed by the measure of the judicial control or the case of the commission of new offenses, it is questionable to replace the judicial check with a heavier preventive measure, namely preventive arrest or home arrest. The present study aims to adress the steps to be followed in this procedure and to analyze the relevant issues and incidents which may arise.